(untitled) (Panacea Journal of Medical Sciences, 2024)
Objectives: To assess how COVID-19 pneumonia differs from other pneumonias in terms of the chest computed tomography features. Materials and Methods: In this study we included 170 clinically diagnosed cases pneumonia referred to department of radio diagnosis subjected to HRCT thorax which include out patients and in patients out of which 127 patients tested RT-PCR positive for Covid 19 pneumonia for a total duration of 1 year. (March 2020 to March 2021). The parenchymal abnormalities including Ground glass opacities (GGO), ground glass opacities with interlobular septal thickening (crazy paving), GGO with consolidation, consolidation, pulmonary nodules, tree in bud appearances, bronchiolar wall thickening, interlobular septal thickening , halo sign, reverse halo sign, cavitation and pleural effusion and were observed and categorized along with determination of pattern of distribution on chest CT. Results: 127 patients who tested positive for COVID 19 and 43 patients with other pneumonia (such as community-acquired pneumonia) were visited, and CT scans were analysed to determine the presence and distribution of the disease pattern. Patients with COVID 19 pneumonia primarily have peripheral-based lesions (90%), whereas patients with other pneumonias primarily have mixed patterns (70%)—a difference that is statistically different (p 0.05). Statistics show that COVID 19 had higher bilateral involvement than other pneumonia (p<0> Conclusion: In COVID-19 pneumonia, GGOs, GGOs with interlobular septal thickening (crazy paving), and GGOs with consolidation with peripheral and basal predominance in bilateral lung parenchyma are the most common imaging patterns and findings. These findings will help us distinguish COVID-19 pneumonia from other causes of pneumonia. There is less evidence of tree in bud, pure consolidation, cavitation, and bronchiolar wall thickening.